Real‐World Treatment Trajectories Following Near‐Infrared Photoimmunotherapy in Head and Neck Cancer: Implications for Clinical Decision‐Making - Ryota Iinuma; Tomohiro Hasegawa; Takuro Tsunoki; Hiroshi Okuda; Ryoukichi Ikeda; Takenori Ogawa (Head & Neck, 2026)
ABSTRACT Purpose Near‐infrared photoimmunotherapy (PIT) is a relatively new locoregional treatment for head and neck cancer. However, real‐world data on its use in clinical practice, particularly regarding treatment trajectories, remain limited. This study described the clinical patterns following PIT in a real‐world setting. Methods This retrospective single‐center case series included 12 patients with head and neck cancer treated with PIT. Patients were grouped into four patterns based on their clinical courses: planned repeated PIT, sequential systemic therapy, early discontinuation, and local control with functional compromise. Clinical characteristics and outcomes were analyzed descriptively. Results Clinical courses after PIT were heterogeneous, and four distinct patterns were observed. Five patients (42%) underwent planned repeated PIT, typically for bulky or extensive mucosal disease. Four patients (33%) transitioned to systemic therapy, mainly immune checkpoint inhibitors, due to residual or metastatic disease. Two patients (17%) discontinued treatment early because of rapid progression or complications. One patient (8%) achieved local tumor control but developed significant functional impairment due to fistula formation. No treatment‐related mortality was observed. Conclusions PIT may be a versatile treatment option in head and neck cancer. Treatment trajectories after PIT varied substantially and may thus provide clinically relevant information for subsequent decision‐making. PIT may be best implemented as a flexible component within an individualized multimodal treatment strategy. These findings provide preliminary real‐world evidence to inform patient selection and treatment sequencing following PIT.